BENEFIT OF YOUTUBE USAGE AND ITS EFFECTIVENESS IN TEACHING ENGLISH: A SYSTEMATIC REVIEW - Siti Afifah Faziah; Shinta Audri Fitriah; Zaennisa Kamila Ramadhan; Naf’an Tarihoran (ADIBA : JOURNAL OF EDUCATION, 2024)
Integrating digital technologies, particularly YouTube, into English language teaching has garnered significant attention in recent years due to its potential to enhance language learning experiences. This article explores the benefits and effectiveness of YouTube in teaching English, providing insights for educators, learners, and researchers. This study adopted a systematic review design, searching for articles using sources such as Google Scholar with 26 articles, Directory of Open Access Journals (DOAJ) with six articles, and Education Resources Information Center (ERIC) with 98 articles. The total number of articles from these three sources was 130 articles. Then, we used PRISMA to filter articles that met our criteria; 12 articles met the requirements, and we will use them. Articles selected were systematically organised, and data analysis was conducted using thematic and content analysis approaches. The review highlights the multifaceted benefits of incorporating YouTube into language teaching, including improving students' language skill development. However, challenges such as inadequate digital skills among educators and contextual factors necessitate careful consideration in leveraging YouTube effectively for language instruction.